2013
DOI: 10.7202/1016060ar
|View full text |Cite
|
Sign up to set email alerts
|

Changement des états de surface, précipitations automnales et vulnérabilité des sols dans le bassin versant du Bouregreg au Maroc

Abstract: International audienceLocalisé dans la région de Rabat-Salé-Zemour, le bassin versant du Bouregreg est un espace essentiellement pastoral dans ses parties intérieures montagneuses et une zone agro-pastorale en aval. Les dynamiques paysagères observées sur ce bassin versant, à l’instar de la plupart des bassins versants du Maroc atlantique, sont marquées par une densification des zones de cultures dans les plaines et de leur extension sur les versants. La classification supervisée des images Landsat de 1987 et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The reduction in plant cover and the openness of the surface as well as its compaction lead to a decrease in the capacity of water to infiltrate the soil. Several authors, including [22][23][24], showed that in arid zones, the infiltration capacity of a soil is governed by its surface condition. The reduction in plant cover, the closing of the soil surface (crust) and its compaction are the main factors in the drop in the rate of water infiltration into the soil.…”
Section: Effect Of Abandonment Of Terraces On Soil Infiltration Capacmentioning
confidence: 99%
“…The reduction in plant cover and the openness of the surface as well as its compaction lead to a decrease in the capacity of water to infiltrate the soil. Several authors, including [22][23][24], showed that in arid zones, the infiltration capacity of a soil is governed by its surface condition. The reduction in plant cover, the closing of the soil surface (crust) and its compaction are the main factors in the drop in the rate of water infiltration into the soil.…”
Section: Effect Of Abandonment Of Terraces On Soil Infiltration Capacmentioning
confidence: 99%
“…This will help to understand the interactions among population dynamics, the types of development and surface changes, as in BROU (2005). For this issue, the main question to answer was: "What are multiscalar approaches allowing to identify the relevant spatial scales in the studies concerning the interactions among humans, climate and the environment"? BROU et al (2013) i.e., an extension of the period during which soils are quasibare during the exceptional years of drought. MAHÉ et al, (2012) completed a study on the Bouregreg by studying the effects of climate variability on water and edaphic condition of the Bouregreg watershed related to human activities, mainly agriculture and grazing.…”
Section: Multiscale Approaches and Modes Of Apprehension Geographicalmentioning
confidence: 99%